Digestibility and protein utilization responses of soybean and rape seed meal to physical and enzymatic treatments in diets for growing pigs - Näsi, Matti (Agricultural and Food Science, 1991)
The effects of extrusion, hydrothermal processing and enzyme pretreatment of soybean meals (SBM) and rapeseed meals (RSM) and the multienzyme supplementation of diets on nutrient digestibility, protein utilization and performance were investigated in growing pigs. The study was comprised of two separate total-collection digestibility and balance trials with 6x6 Latin square designs and a production trial with 140 growing pigs. The processes employed had only minor effects on the chemical composition of the treated oilseed meals. Extrusion and addition of enzyme premix improved the organic matter (OM) and protein (CP) digestibilities of SBM (P<0.05). These processes also tended to have a positive effect on the nitrogen retention and protein utilization in the pigs. The hydrothermal process had no effect on the nutritive value of SBM, but improved the OM and CP digestibility in RSM (P<0.05). Energy values of the treated SBM and RSM tended to increase compared with the untreated meals. There were no significant differences in growth rate, feed conversion or carcase quality between pigs fed diets supplemented with differently treated SBM, relative to untreated control. Partial hydrolysis of the polysaccharides present in SBM and RSM with hydrothermal or enzymatic processing may have resulted in the release of intracellular nutrients in the intestine and improved their absorption and utilization. More consistent responses to these thermal and enzymatic treatments could be expected with younger pigs with less microbial activity in the alimentary canal.